Analysis of Risk Management that Affects The Reconstruction Project of The West Java Provincial Road Section using The Severity Index (SI) Method - Sahrul Maulana; Reynald Siswanto; Agung Gunawan; Lutfi Marantica; Sumarman Sumarman (Jurnal Syntax Transformation, 2025)
Road damage on provincial roads in Cirebon Regency disrupts community mobility and has the potential to cause accidents. This problem requires reconstruction measures to improve transportation safety and efficiency. This study aims to identify the dominant risks affecting the implementation of provincial road reconstruction projects in West Java using the Severity Index (SI) method. The research approach used is quantitative. Data were collected through a questionnaire survey distributed to project owners, consultants, and contractors directly involved. Severity Index method was applied to assess and calculate risks based on probability impact matrix (PIM). From the analysis, 12 risk factors with 22 risk variables were found to have high severity and unacceptable. These risks include political, environmental, planning, financial, and technical aspects, which have a significant effect on project time, cost, and quality. Provincial road reconstruction in West Java faces various risks that must be effectively managed to achieve success. Proposed risk mitigation includes expert consultation, development of a coordination plan, and worker training to improve communication and safety awareness. These measures are expected to ensure the project goes according to plan and minimize any negative impacts that may occur.